Inovasi Nasi Gigit Udang Asam Manis : Solusi Pangan Sehat dan Sumber Pendapatan Bagi Ibu Rumah Tangga di RT.5 Kelurahan Kampung 6 - Nurul Hidayat; Anggun Sarwana; Sulaiman Sulaiman; Eva Riana; Mengsi Mengsi; Ilham Ilham; Hilda Hilda (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
The "Sweet and Sour Shrimp Rice Bites" innovation program is an empowerment effort aimed at housewives in RT 5, Kampung 6 Sub-district, through the development of a healthy, locally-based food product. This innovation seeks to create a nutritious and practical food alternative that appeals to various groups, while also serving as an additional source of household income. The product combines carbohydrates from rice, protein from shrimp, and a signature sweet and sour flavor, packaged in small, hygienic, and easy-to-consume portions. Training activities in production, packaging, and marketing were conducted participatively with the housewives, using a creative economy approach and local wisdom. The program results show increased skills, confidence, and economic contribution from participants. This innovation has proven to be both a healthy food solution and a support for household economic independence in the community